Excavations at Dor: figurines, cult objects and amulets 1980 - 2000 seasons - Shṭern, Efraim (The Institute of Archaeology, Hebrew University of Jerusalem, 2010)
Pt. 1. Figurines and cult objects of the Iron age and Persian period / Ephraim Stern -- Pt. 2. Figurines, sculpture and minor art of the Hellenistic and Roman periods / Adi Erlich -- Pt. 3. The cult of Nemesis : the griffin in marble and clay / Renate Rosenthal-Heginbottom -- Pt. 4. Egyptian faience amulets / Christian Herrmann